Malignant pilomatrixoma case report: what kind of treatment is the most suitable? - Emeršič, Luka; Stritar, Albin; Jurčić, Vesna (International Journal of Research in Dermatology, 2022)
Malignant pilomatrixoma is a rare malignancy with just 136 cases reported in the English literature. The tumour is described as locally aggressive, with possibility of reoccurrence and distal metastasis. Histology remains the gold standard in diagnostic. Wide surgical excision is preferred to simple excision. In the present study a case of first malignant pilomatrixoma in our hospital is described. We made an excision of the tumour and the tissue was sent on histopathology. The skin defect was covered with a local ulnar flap. Through our case report and literature review we focus on the most suitable treatment option. The tumour was not excised with appropriate safety surgical margin based on the histopathology report. Patient refused another excision and any additional treatments. The most optimal treatment has not yet been established. Most of the article’s state that primary wide surgical excision should be done, with surgical margins still being debateable. The best results were given when using Mohs micrographic surgery.